98.0k views
5 votes
For the function f(x) = (25 – 10), find f-'(x). of-1(x) = (V)+10 3 of-'(x) = V(x + 10) of-1(x) = x3 + 10 f-1(x) = x3 + 10

For the function f(x) = (25 – 10), find f-'(x). of-1(x) = (V)+10 3 of-'(x) = V(x + 10) of-example-1

1 Answer

2 votes

Answer::


f^(-1)(x)=\sqrt[5]{x^3+10}

Step-by-step explanation:

Given f(x) defined below:


f(x)=(x^5-10)^{(1)/(3)}

To solve for the inverse, follow the steps below:

Step 1: Rewrite the equation using y.


y=(x^5-10)^{(1)/(3)}

Step 2: Next, swap x and y:


x=(y^5-10)^{(1)/(3)}

Step 3: Solve for y.


\begin{gathered} x^3=y^5-10 \\ y^5=x^3+10 \\ y=\sqrt[5]{x^3+10} \end{gathered}

Step 4: Replace y with the inverse function:


f^(-1)(x)=\sqrt[5]{x^3+10}

User Adam Wagner
by
4.8k points